EFFECTIVENESS OF MISSOURI MATHEMATICS PROJECT (MMP) LEARNING MODEL AND COOPERATIVE LEARNING MODEL OF NUMBERED HEADS TOGETHER (NHT) LEARNING ON THE MATHEMATICS LEARNING OUTCOME - Maya Merina; Harina Fitriyani (Universitas Ahmad Dahlan, 2018)
Mathematics learning at SMP Negeri 15 Yogyakarta used speech method and given questions that impact making students bored when mathematics learning. Used the wrong model to make students are challenging to develop and also to the learning outcome. So, we need the right model. The model is an MMP and cooperative learning type NHT. This research aims to find a significant difference between the use of MMP learning with the use of cooperative learning type NHT, which is better MMP learning than NHT cooperative learning to the student's mathematics learning outcome. This research population was the seventh degree of SMP Negeri 15 Yogyakarta consisting of ten classes and two classes as the sample with random sampling. The sample is VII B as the experiments A with MMP learning and VII D as the experiment B with cooperative learning type NHT. The research instrument used was a mathematics learning outcome, and analysis used validity, distinguishing capacity, and reliability. The data analysis used was the t-test two parties and one party. Based on the analysis of the first hypothesis test on mathematics learning outcome with a significance level of 5% and 65 degrees of freedom is obtained Â so Â then there is a significant difference between the use MMP learning with the use cooperative learning type NHT. The second test with a significance level of 5% and 65 degrees of freedom is obtained , so Â then MMP learning better than NHT cooperative learning to the student's mathematics learning outcome.